PENGARUH LABA KOTOR, LABA OPERASI DAN LABA BERSIH TERHADAP ARUS KAS MASA DEPAN - Rianta Magdalena Pangaribuan,; Puspita Rama Nopiana, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
Cash flow is very useful for assessing the company's ability to generate cash and cash equivalents. This study aims to examine whether there is an influence between gross profit, operating profit and net income on future cash flows. The data used are the financial statements of the food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange (IDX) with a research sample of 54. This analysis uses a purposive sampling method with multiple linear regression analysis techniques. The results showed that gross profit has no significant and positive effect in predicting cash flow with a significance value of 0.604> 0.05. Operating profit has a negative and significant effect on future cash flows with a significant value of 0.006 <0.050. Net income has a positive and significant effect on future cash flows 0.000 <0.05, which means that the research hypothesis of net income (X3) has a positive and significant effect on future cash flows (Y). Simultaneous test (F test) shows that gross profit, operating profit and net income have a significant effect on cash flow with a significant value of 0.000 <0.05